The multiple mediation of market intelligence and competitive intelligence in enhancing the relationship between intelligent systems and processes and the competitiveness of start-ups - Zighed Rahma; Ismail Bengana; Mekimah SABRI; Khaled Mili; Musaddag Elrayah (Telematics and Informatics Reports)
This study explores how technological intelligence enhances the competitive advantage of Algerian start-ups. It offers new insights into how intelligent systems and processes can support decision-making and improve performance. The study aims to fill a scientific gap characterized by a lack of understanding regarding the impact of these elements on the competitive capacity of start-ups, highlighting the need for a comprehensive study. Additionally, the research seeks to analyze the relationship between technological intelligence and competitive advantage by examining the effects of competitive intelligence and market intelligence. To achieve this, we employed a methodology that includes collecting and analyzing quantitative and qualitative data from a random sample of 357 start-ups in Algeria.The results indicate a statistically significant positive effect of 21.30 % between intelligent systems and processes and both market intelligence and competitive intelligence, thereby enhancing the competitive capacity of start-ups. The implications of these findings underscore the necessity for start-ups to invest in developing intelligent systems and processes, as well as enhancing competitive intelligence and market intelligence to increase their competitiveness. Furthermore, this could lead to the development of effective strategies to improve institutional performance, contributing to innovation and economic growth in the Algerian market.